2017
DOI: 10.1161/hypertensionaha.117.09458
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-Wide Analysis Identifies Novel Associations With Blood Pressure

Abstract: Hypertension represents a major cardiovascular risk factor. The pathophysiology of increased blood pressure (BP) is not yet completely understood. Transcriptome profiling offers possibilities to uncover genetics effects on BP. Based on 2 populations including 2549 individuals, a meta-analyses of monocytic transcriptome-wide profiles were performed to identify transcripts associated with BP. Replication was performed in 2 independent studies of whole-blood transcriptome data including 1990 individuals. For iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 43 publications
3
25
1
Order By: Relevance
“…In contrast, Gilz overexpression may lead to a moderate increase in sodium reabsorption and a subtle increase in arterial blood pressure that could predispose patients to the development of hypertension. Interestingly, Gilz has been identified as a gene associated with blood pressure variations and hypertension-related cardiac phenotype, as well as a molecular marker of thiazide response in patients with hypertension, in large transcriptome-wide analysis studies in humans 39,40 . Thus, Gilz could be considered a susceptibility gene that participates in the complex pathophysiology of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Gilz overexpression may lead to a moderate increase in sodium reabsorption and a subtle increase in arterial blood pressure that could predispose patients to the development of hypertension. Interestingly, Gilz has been identified as a gene associated with blood pressure variations and hypertension-related cardiac phenotype, as well as a molecular marker of thiazide response in patients with hypertension, in large transcriptome-wide analysis studies in humans 39,40 . Thus, Gilz could be considered a susceptibility gene that participates in the complex pathophysiology of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Lamins are type V intermediate filament proteins that form the nuclear lamina, a filamentous network underlying the inner nuclear membrane of eukaryotic cells . Mutation, aberrant splicing and abnormal expression of lamin A/C, the nuclear A‐type lamins, will lead to the disruption of various crucial cellular functions and result in a number of devastating diseases. For example, in the cardiovascular system, mutation of lamin A/C caused by Lmna mutations participates in up to 10% of dilated cardiomyopathies (DCMs) and underlies a spectrum of other diseases including muscular dystrophy, lipodystrophy and acrogeria syndromes .…”
Section: Discussionmentioning
confidence: 99%
“…Under hypertension, the repression of lamin A/C has been shown to be a potential biomarker that is associated with blood pressure changes . Maggi et al also reports that abnormalities in lamin A/C cause hypertension .…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study has found different pathway regulations between RIF and RM [ 12 ]. Furthermore, whole blood transcriptome studies could reveal other physical changes of human body, like blood pressure [ 13 ], pre-term labor [ 14 ], or immune response [ 15 ]. However, none of the earlier studies applied this technique to compare and correlate the transcriptome profiles of endometrium and peripheral blood and examine the potential usefulness of transcriptome study of peripheral blood to characterize different groups of women with reproductive failure.…”
Section: Introductionmentioning
confidence: 99%